2016
DOI: 10.1021/acs.chemrev.6b00037
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrogen Complexation

Abstract: Dihydrogen complexation with retention of the H-H bond, once an exotic concept, has by now appeared in a very wide range of contexts. Three structural types are currently recognized: Kubas dihydrogen, stretched dihydrogen, and compressed dihydrides. These can be difficult to distinguish, hence the development of a number of novel spectroscopic methods for doing so, mainly based on NMR spectroscopy. Three important reactivity patterns are identified: proton loss, oxidative addition, and dissociation, each of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
164
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(184 citation statements)
references
References 190 publications
10
164
0
Order By: Relevance
“…Although we as yet have no direct evidence as to the structure of the observed B intermediate (Fig 4), as visualized in Fig 6 the behavior of inorganic H 2 complexes 3032 indicates that this intermediate is an H 2 -bound state on the ground adiabatic potential-energy surface, a possibility first noted thirty years ago. 33 Firstly, thermally induced re/oa of inorganic H 2 complexes generally proceed through such an intermediate, 23 indicating an expectation that such a state is present on the ground adiabatic surface as shown in Fig 6.…”
Section: Resultsmentioning
confidence: 87%
“…Although we as yet have no direct evidence as to the structure of the observed B intermediate (Fig 4), as visualized in Fig 6 the behavior of inorganic H 2 complexes 3032 indicates that this intermediate is an H 2 -bound state on the ground adiabatic potential-energy surface, a possibility first noted thirty years ago. 33 Firstly, thermally induced re/oa of inorganic H 2 complexes generally proceed through such an intermediate, 23 indicating an expectation that such a state is present on the ground adiabatic surface as shown in Fig 6.…”
Section: Resultsmentioning
confidence: 87%
“…36 Furthermore, the disappearance of 2 upon warming is consistent with the well-known lability of dihydrogen as a two-electron-donor ligand. 37 Complex 2 is an analogue of Ru(H) 2 41,42 In order to confirm the presence of a dihydrogen ligand in 2, data for T 1 were recorded at 400 MHz between 212 and 242 K for the resonance at δ −5.82. The value of T 1 (min) for 2 proved to be 35 ± 2 ms at ca.…”
Section: H{mentioning
confidence: 99%
“…Exposure of ab enzene solution of 4 to H 2 (1 bar) at 70 8 8Cf or 5h resulted in ac olorless solution, from which compound 5 was isolated as aw hite powder in 72 %y ield. [2,12] Tr eatment of 4 with one equivalent of DCNxyl (xyl = 2,6-dimethylphenyl) in toluene at room temperature led instantaneously and cleanly to the formation of compound 7.The 11 BNMR spectrum of 7 displayed broad singlets at 3.6 ppm and À12.9 ppm. Thesolid-state IR spectrum of 5 exhibited two characteristic B À Hv ibrations at 2442 and 2326 cm À1 .X -ray diffraction revealed that two boron-bound hydrogen atoms are attached on the same side of the B 2 C 2 N 2 six-membered ring, the selectivity of which is similar to that for I.…”
Section: Zuschriftenmentioning
confidence: 99%